My Voice, My Choice: A systematic review of the literature relating to consumer-directed care in Australia - Jennifer Kosiol; Richard Olley; Sheree Lloyd; Linda Fraser; Helen Cooper; Daniel Waid (ACHSM, 2024)
Objectives and importance of study: The objective of this systematic review of the literature was to examine the evidence relating to consumer-directed care (CDC) in the aged care environment. CDC entails providing individuals with the option of choice and flexibility in their care, to empower aged care recipients with autonomous decisions over their healthcare choices. Additionally, the researchers found evidence relating to the vulnerability of users of aged care services and the lack of understanding towards a true consumer-oriented approach which was highlighted during the Royal Commission into Aged Care Safety and Quality. Study type and method: The research team used the PRISMA Method to review the available literature systematically. This qualitative review of the literature on consumer choice in the aged and social care sectors assessed sixteen high-quality research papers and identified themes that emerged to promote authentic consumer voice in aged care services. These articles provided insight into what aged care providers require to increase transparency and facilitate effective, meaningful consumer choice. Results: Six themes emerged from the literature reviewed: Informed Choice, See Me Hear Me, Funding My Choices, My Choice My Way, Policy, and Know Me, Include Me. The authors found significant challenges to authentic consumer voice in terms of reliable information, complex, inflexible service provision, and a trusted and skilled carer workforce. Conclusion: Authentic consumer choice requires collaboratively designed care plans with consumers, integrating their care-related preferences and values. Providers who have embraced CDC principles, and innovative practices have enhanced person-centred care, and consumer experience and autonomy. Cultivating inclusive, transparent, and collaborative environments to empower older Australians to shape and control their care provision and wellbeing is a key challenge for providers.